1982
DOI: 10.1002/em.2860040407
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity screening of foods I. Results with beverages

Abstract: Following a number of recent reports on the presence of mutagens in certain foods, a general survey of the mutagenic potential of a wide variety of food products has been initiated. Here, results for samples of 28 widely consumed beverages from 13 general categories are reported. Each sample was concentrated and fractionated by polarity and solubility to give up to seven fractions, each of which was assayed for mutagenic potential with Salmonella typhimurium TA98 and TA100 +/- fortified liver homogenate. Fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…They recommended that the genotoxic impact of the saccharin may be because of the salts particles. On the other hand the positive mutagenic results of saccharin might be due to the impurities of the saccharin which showed greater mutagenic effects on TA98 than TA100 strains of Salmonella typhimurium [16].…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that the genotoxic impact of the saccharin may be because of the salts particles. On the other hand the positive mutagenic results of saccharin might be due to the impurities of the saccharin which showed greater mutagenic effects on TA98 than TA100 strains of Salmonella typhimurium [16].…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenic activity in bacterial tests has been reported in several kinds of beverages. Stoltz et al [1982] investigated 28 different beverage products and found mutagenic activity in grape juice, red wine, and instant coffee. The mutagenic activity in grape juice and red wine was due to the presence of flavones, e.g., quercetin and kaempferol.…”
Section: Instant Coffeementioning
confidence: 99%
“…This was also shown by Mazaki et al [1982], who found flavones in mutagenic hydrolysates from citrus fruit juices. Stoltz et al [1982] found a chocolate drink to have some mutagenic potential, while tea was not mutagenic. The mutagenic activity in coffee has been the subject of many studies, and the results are somewhat contradictory.…”
Section: Instant Coffeementioning
confidence: 99%
See 1 more Smart Citation
“…4) Stolz et a1. 15 have found that x 3 concentrates derived from such popular beverages as red wine, grape juice and coffee are mutagenic to Salmonella. These mutagens are thus several times more potent than water contrates, and reflect the view that diet per se is probably much more significant as a contributor to life style and cancer burden than drinking water.…”
Section: Ames Test As Applied T O Aqueous Samplesmentioning
confidence: 99%